Effect of thermal bridges on the energy performance of Chinese residential buildings - Guojie Chen; Yifan Hou; Hua Ge; Shuyan Zhang; Xiangwei Liu; Xingguo Guo; Dong Xie (Energy and Built Environment)
Thermal bridges may represent up to 50 % of the building's envelope area and may increase the energy consumption of buildings by up to 30 %, however their impact is often not taken into account adequately in China. In this study, the energy performance of a typical two-story residential building under four different Chinese climate zones is investigated using WUFI Plus program in terms of annual heating and cooling energy demands. Several typical thermal bridges were taken into consideration. Two methods were used to evaluate the effect of thermal bridges on the building energy performance, the simplified method commonly used in China and the dynamic 3D modelling method, and were compared to do not consider thermal bridge. Also, two different types of building envelope, brick wall and aerated concrete wall, were used to evaluate the effect. The results show that by taking into account the thermal bridges, the annual heating energy demands of residential building increase 21.2 %, 24.8 %, 27.8 %, and 16.6 % under the four Chinese climate zones. Therefore, attention should be paid in the building envelope design to reduce thermal bridges. Compared to the dynamic 3D modelling method, the simplified method underestimates annual heating and cooling energy demands.